A retrospective review of antiphospholipid syndrome from a South Asian country - Muhammad Zain Mushtaq,; Syed Ahsan Ali,; Zaibunnisa Sattar,; Saad Bin Zafar Mahmood,; Tazein Amber,; Mehmood Riaz, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate clinical presentations, antiphospholipid antibody patterns and their levels, therapeutic regimens, and outcomes in patients with antiphospholipid syndrome (APS) admitted to a tertiary care hospital of a South Asian country. Patients and methods: Between January 2009 and December 2019, a total of 216 patients with APS (8 males, 208 females; median age: 35.7±6.9 years; range, 20 to 76 years) who either fulfilled the modified Sydney criteria or those who satisfied only clinical criteria along with positive antiphospholipid antibody on at least one occasion (probable APS) were retrospectively analyzed. Results: The majority of the patients (n=183, 84.7%) had obstetric complications, followed by venous thrombosis in 23 (10.8%) patients. Recurrent early abortions in 126 (58.6%) and deep venous thrombosis in 16 (7.4%) patients were the most prevalent obstetrical and venous events, respectively, whereas limb gangrene in seven (3.3%) and ischemic stroke in seven (3.3%) were the most common arterial events. A total of 190 (88%) patients had primary APS, while 26 (12%) had secondary APS. Systemic lupus erythematosus was the frequent association with secondary APS found in 19 (73%) patients. Immunoglobulin M (IgM) anticardiolipin antibody was present in 173 (65.0%) patients, being the most commonly reported antibody. Probable catastrophic APS was found in four (1.9%) patients. Majority of the patients (n=190, 87.9%) were treated with a combination of acetylsalicylic acid and low-molecular-weight heparin. Single mortality was observed in our study population due to complications related to catastrophic APS. Conclusion: Antiphospholipid syndrome has a wide range of thrombotic and obstetrical manifestations with important variations in different regions of the world. There is a significant morbidity and mortality related to APS, despite treatment with anticoagulation and; therefore, describing prognostic markers and optimal therapeutic interventions is pivotal to prevent complications.